Partisipasi ASN Dalam Penerapan Asas Netralitas Terhadap Pemilihan Umum - Anang Setiyawan; Rido Pramono (International Forum of Researchers and Lecturers, 2024)
The neutrality of ASN in elections is something that the government needs to pay attention to and supervise. Because the principle of neutrality is an obligation for ASN to be implemented properly and correctly. From the election moment in the previous period, it is evident that there is a need for reaffirmation both in the form of regulations and supervision. Bawaslu has the duty and authority to prevent and take action against ASN who commit neutrality violations. So this research uses the Normative Juridical Method whose approach uses a statutory approach. The aim of this research is to find out the legal basis that regulates ASN neutrality in elections and how Bawaslu will act in dealing with violations of ASN neutrality in elections.